'Awaken your incredible': Love your body discourses and postfeminist contradictions. (1st June 2014) - Gill, Rosalind; Elias, Ana Sofia
In this article we focus on a new yet under-examined cultural phenomenon: the turn to 'Love your body' (LYB) discourses. Taking a feminist critical standpoint, we move away from an affirmative reading of LYB discourses and instead understand them as a postfeminist articulation of sexism. Our analysis identifies the key motifs of LYB discourses and contextualizes their dramatic proliferation over the last decade. Situated at the historical convergence of neoliberal governmentality, emotional capitalism, the growth of social media and commodity feminism, we trace how LYB discourses have emerged within the advertising genre to quickly saturate media more broadly. The article concludes with a critical assessment of LYB discourses that seeks to flesh out its distinctive contradictions and its ideological workings. In so doing, we will argue that far from representing a liberation from harmful beauty standards, LYB discourses are implicated in a deeper and more pernicious regulation of women that has shifted from bodily to psychic regulation.